THE ROLE OF STRATEGIC AWARENESS IN ACHIEVING ADMINISTRATIVE REFORM-AN ANALYTICAL STUDY IN THE INTEGRITY DIRECTORATES IN IRAQ - Hayder Jaber Alghelany; Raoudha Kammoun (Scholars Digest Publishing, 2023)
The research aimed to identify the role of strategic awareness in its three dimensions (reflection, systems thinking, learning orientation, and reformulation) in achieving administrative reform in its six dimensions (organizational development, comprehensive quality management, performance evaluation, training, transparency, and responsiveness) in the Iraqi Integrity Commission. Based on a major problem diagnosed with several questions that included the extent of awareness of the influential relationship between the two variables in the field, the research sample included 180 individuals working in the Authority. Iraqi Integrity The descriptive analytical approach was mainly adopted in presenting, analyzing and interpreting the research information. The questionnaire was used as a main tool for collecting data and research information, in addition to some personal interviews with members of the research sample, who were represented by a group of leaders and followers of the Iraqi Integrity Commission. These methods were used using statistical programs (SPSS, Amos). Many conclusions were reached through the research, the most important of which was the interest of the Integrity Commission, the research sample, in applying and implementing awareness strategies and policies. Field strategy that would modify or enhance the effect of strategic awareness in administrative reform, so that the presence of strategic awareness in the field, in addition to the adoption of strategic awareness by the Integrity Commission departments, would improve the level of achieving administrative reform. The current research has yielded a set of recommendations, the most important of which is the need for the Integrity Commission departments to take measures, the most important of which is working to increase interest in strategic awareness among departments at various levels in order to achieve administrative reform.
Keywords: strategic awareness, administrative reform,reformulation